Academic self efficacy and social support for academic burnout in islamic boarding school students - Nurhidayah, Siti; Hanoum, Magdalena; Arlinda, Ita (Educenter : Jurnal Ilmiah Pendidikan, 2024)
This research aims to determine the relationship between academic self-efficacy and academic burnout and social support on academic burnout in santris, as well as the influence of academic self-efficacy and social support on academic burnout in santris. This research is research using quantitative research methods with a correlational type. The subjects in this research were santris at the Bekasi Islamic boarding school. The sampling technique used was a random sampling technique and the number of samples used was 156 using the Slovin formula with a precision value of 0.05. The data collection methods in this research are interviews and psychological measurement scales. The research instruments used were the academic self-efficacy scale with an Alpha Cornbach reliability value of 0.953, the social support scale with an Alpha Cornbach reliability value of 0.854, and the academic burnout scale with an Alpha Cornbach reliability value of 0.880. Data analysis techniques used the Spearman rank correlation test and regression test. multiple linear. This research found that academic self-efficacy and academic burnout had a negative relationship, namely -0.217, and social support and academic burnout had a negative relationship, namely -0.331. Furthermore, there is an influence between academic self-efficacy and social support on academic burnout showing an R square (R2) value of 0.128 or 12.8%.